Causes and Countermeasures of Difficult Selective Biliary Cannulation: A Large Sample Size Retrospective Study. Issue 5 (16th October 2021) - Liu, Yang; Liu, Wei; Hong, Junbo; Li, Guohua; Chen, Youxiang; Xie, Yong; Zhou, Xiaojiang
Abstract : Objective: Selective biliary cannulation is a difficult part of endoscopic retrograde cholangiopancreatography (ERCP). Therefore, endoscopists have focused on how to improve the cannulation success rate and reduce the postoperative complication rate. This study aims to provide practical advice on safe operation for endoscopists. Materials and Methods: Data from the ERCP database of our medical center from January 2008 to December 2017 were retrospectively reviewed. All patients underwent ERCP for the first time. Data pertaining to diseases, anatomic factors, difficult cannulation rates, cannulation success rates, and postoperative complication rates for various assistive cannulation techniques were analyzed by using the Pearson χ 2 tests and Fisher exact tests. Results: The difficult cannulation rate was 8.1%. The main influencing factors were benign and malignant biliary stricture, duodenal papillae or ampullary tumors, thick and long duodenal papillae, peridiverticular papillae, ectopic papillae, edematous papillae, ulcerative papillae, anomalous pancreaticobiliary junction, and Billroth II gastrectomy. The postoperative complication rates and overall cannulation success rates of 7 assistive techniques were not statistically different ( P >0.05), but the overall complication rates were statistically different ( P <0.05). Needle-knife precut sphincterotomy had the highest rate of complications. Conclusions: Benign and malignant biliary stricture, duodenal papillae or ampullary tumors, thick and long duodenal papillae, peridiverticular papillae, ectopic papillae, edematous papillae, ulcerative papillae, anomalous pancreaticobiliary junction, and Billroth II gastrectomy were the main factors of difficult selective biliary cannulation. The overall incidence of needle-knife precut sphincterotomy complications was higher than that of other techniques, but various assistive techniques were safe and effective in our single center.